Implementation of remote general movement assessment using the in-motion instructions in a high-risk norwegian cohort - Lars Adde; Kristin Bjørnstad Åberg; Toril Fjørtoft; Kristine Hermansen Grunewaldt; Randi Lade; Siril Osland; Frank Piegsa; Per Gunnar Sandstrøm; Ragnhild Støen; Gunfrid V. Størvold; Beate Horsberg Eriksen (BMC Pediatrics, 2024)
Abstract Background General Movement Assessment (GMA) is recommended for early detection of risk for cerebral palsy but requires trained clinical experts. We aimed to implement home- and hospital-based filming for remote GMA in a Norwegian high-risk infant cohort, as well as evaluating parents’ experiences in filming their infant at home. Methods This knowledge translational study used a prospective cohort design including participants referred to neurodevelopmental follow-up across three sites in the Central Norway Regional Health Authority. Two home films of the fidgety type of general movements were collected between 12+1–14+6 and 15+1–17+6 weeks after term by parents. An additional film was collected at the hospital between 12+1 and 17+6 weeks after term. The instructional guide for all filming was the In-Motion App standards. Videos were transferred to a remote GMA team and classified as either “GMA scorable” or “GMA not scorable” based on Prechtl’s GMA standards. Parents responded to an online survey using a 5-point Likert scale to collect information about their perspectives, experiences, and possible worries by filming their infant at home. Results One-hundred-and-two infants from 95 families participated. Ninety-two (96.8%) families transferred 177 home-based videos. Eighty-four (92%) of these had 95 videos taken in their local hospital. All 177 home-videos were “GMA scorable” and three (3,1%) out of 95 hospital-based videos were classified as “GMA not scorable”. Eight families did not respond to the survey and two families did not receive the survey due to a technical error. Seventy-eight (91.7%) respondents agreed or strongly agreed that it was easy to perform home filming and five (5.9%) agreed that they were more worried about their child`s development after filming at home. Almost 80% of respondents agreed that a video for GMA can be taken at home instead of in hospital. Conclusions This study strengthens the clinical implementation of home filming by parents and remote GMA for early detection of CP in high-risk follow-up programs. The implementation of remote GMA has the potential to facilitate early intervention to improve function in children with CP in line with international recommendations. Trial registration ClinicalTrials.gov ID: NCT04287166 Date of registration: 27/02/2020.